Resilience and emotional intelligence as mediators between personal values and life satisfaction among Chinese young adults - Lv, Fangyan; Tan, Jingbin; Shi, Dongzhe; Gao, Dingguo (Frontiers in Psychology, 2024)
Background: Young adults are in the period of the formation and establishment of values. Even though previous research has revealed that personal values are important factors influencing young adults' life satisfaction, it is still unknown when and under what circumstances values affect life satisfaction among young adults. Therefore, this study explored the relationship between personal values and life satisfaction among Chinese young adults, focusing on the mediating roles of resilience and emotional intelligence.Methods: A sample of N = 635 (271 male) young adults from four universities located in Guangzhou were recruited using a cross-sectional stratified sampling method. All participants completed the Revised Portrait Value Questionnaire, Emotional Intelligence Scale, Satisfaction with Life Scale, and Brief Resilience Scale.Results: Results revealed that: (1) self-transcendence (r = 0.29, p < 0.001), self-enhancement (r = 0.27, p < 0.001), openness to change (r = 0.22, p < 0.001), and conservation (r = 0.26, p < 0.001) were differentially positively associated with life satisfaction. Chain mediation analysis found that: there was a significant indirect effect for self-transcendence, via EI (ind = .070, p = 0.004, 95% CI = [.027, .124]), and the sequential influence via EI and resilience suggested a moderate effect (ind = .024, p = .008, 95% CI= [.009, .045]). For self-enhancement values exerted significantly negative indirect effects on LS via resilience (ind = -.029, p = .034, 95% CI= [-.060, -.005]). Openness to change had a significant indirect impact on LS via EI (ind = .086, p < .001, 95% CI = [0.046,0.133]), and the sequential influence via resilience and EI was significant (ind = 0.029, p = .001, 95% CI = [.015, .050]). For conservation, the chain mediation model did not reveal any significant indirect effects via resilience or EI.Our findings extend the current literature on personal values and life satisfaction, highlighting the significant effects of resilience and emotional intelligence on the link between personal values and life satisfaction. Overall, this research helps young adults strengthen their resilience and emotional intelligence to increase the impact of values on life satisfaction.